Analisis Tingkat Kepuasan Layanan Manajemen oleh Tenaga Kependidikan - Wenny Pebrianti (LAMPUHYANG, 2022)
This study aims to measure the level of user satisfaction with services is an important factor in developing a service provision system that is responsive to user needs, costs and time, and maximizes service to users. The results of the assessment to 121 respondents who are education personnel, both civil servants and honorariumsshow that the assessment for job satisfaction and infrastructure is dominated by good answers by 43% and very good by 26%. The assessment for the leadership satisfaction aspect is dominated by good answers by 42% and sufficient by 30%. The assessment for the aspect of work atmosphere is dominated by good answers by 45% and very good by 34%. The assessment for the aspect of career development satisfaction above is a good answer of 39% and sufficient by 31% for the aspect of the Rights of Education Personnel dominated by good answers of 38% and sufficient 28%.